A configuração do poder local institucionalizado em Carambeí e suas perspectivas para o desenvolvimento social municipal - Silva, Silmara Carneiro e (2008)
The Democracy as a hegemonic political system in the modernity becomes a legitimate field in which the relations between the State and Civil Society are realized. It is in these relations, taking part in the representative and participative democratic spaces, that the perspectives on the social development are discussed and assumed by the public sphere in contemporary times. The political culture and the participation of the ones involved in this process are the essential elements for the configuration of the relationships that are built between the hegemonic and antihegemonic fights that take place in the institutionalized power spaces. With these presuppositions, the present research aims at analyzing the configuration of the relationships between the institutionalized local power spaces in Carambeí and its perspective on the municipal social development, considering the involved subjects’ points of view. The research has been realized through the systematization of the theoretical fundamentals based on the referential authors of the Applied Social Sciences and the application of a questionnaire and semi-structured interviews to the significant subjects of Carambeí’s institutionalized local power, connected to the municipal executive, legislature, and councilors of social assistance and work. The conclusion that has been reached indicates the need to strengthen the antihegemony in the local Carambeí’s spaces, through the socialization of the politics and sharing the power among the institutionalized local power spaces in Carambeí. These are considered essential conditions in order to the relationships between the State and Civil Society becoming more horizontal and therefore the different perspectives of municipal social development, indicated by the subjects, may become anti-hegemonic perspectives in the municipal public sphere.